Sertaconazole antifungal profile determined by a microdilution method versus nine topical substances against dermatophyte fungi - Carrillo Muñoz, A. J. (2012)
Antifungal activity and in vitro inhibition time for sertaconazole (STZ) and 9 other topical drugs, namely amorolfine, bifonazole, clotrimazole, econazole, ketoconazole, miconazole, oxiconazole, terbinafine, and tioconazole were determined against 124 clinical isolates of dermatophyte (12 species) fungi by the microdilution method in a liquid medium and the measurement of optical density. STZ's antifungal activity was not always affected by the tested dermatophyte genus, as was the case with the remaining antifungals. In vitro antifungal activity was at the same level for all the studied azole derivatives, but, in terms of partial inhibitory concentrations, STZ starts its in vitro inhibitory activity in a shorter time than the other tested substances, particularly in those incubation periods when the growth of the dermatophyte fungi was more developed.